Bioactive compounds separation with simulated moving bed technology - Ribeiro, Diogo Rafael Pacheco (2019)
The pharmaceutical industry is developing a growing interest in natural compounds with biological and nutritional properties. Betulinic and oleanolic acids are two naturally occurring triterpenic acids, which possess such characteristics. These two compounds can be extracted from natural resources, i.e., from the bark of Eucalyptus globulus. However, their separation is difficult because these compounds present similar structures (they are constitutional isomers). In this work, the chromatographic separation of betulinic and oleanolic acids from representative extracts of E. globulus was studied. High performance liquid chromatography (HPLC) assays were initially performed using an Acclaim C30 column as stationary phase. Through these tests it was found that the mobile phase methanol/acetonitrile 50/50 (%, v/v) is the most suitable for the separation of both triterpenic acids. In order to determine the equilibrium constants () and the global linear driving force mass transfer coefficients (), several breakthrough experiments of pure acids (unary solutions) were carried out. The two parameters were correlated using experimental data and then validated by simulating the breakthrough curve of a binary mixture containing the same proportion of betulinic and oleanolic acids found in E. globulus extracts. The outcomes of all experiments were modeled using Carta’s analytical solution. In parallel, the method of moments was also used to obtain the transport parameters. The results were consistent. Lastly, the separation of betulinic and oleanolic acids by simulating moving bed (SMB) has been studied, carrying out simulations using the transport parameters obtained before from the breakthrough assays. Two different column configurations (1-1-1-1 and 2-2-2-2) and column lengths (from 10 to 25 cm) were adopted. It was concluded that using an SMB unit is able to separate betulinic and oleanolic acids with purity higher than 99 % both in extract and raffinate for all the scenarios presented. Posteriorly, the recovery of both triterpenic acids from the extract and raffinate streams of a future process was also investigated, taking advantage of their low solubility in water. Accordingly, the solubility of each triterpenic acid in solvent mixtures of increasing water concentration was experimentally measured and discussed.